Unified Approach to Environments in a Process Functional Language - Kollár, Ján (Computing and Informatics, 2012)
A process functional paradigm is based on applications of processes and functions instead of assignments. The imperative computation and the functional evaluation are clearly separated in a well-balanced manner, providing the strong feedback about the implementation to a user. In this paper we present the unified approach to explicit and implicit environments in PFL -- an experimental process functional language, as a uniform basis for approved implementation extensible by additional specification. PFL environmental concept is the generalized implementation substance, which can be found in many programming languages exploiting the large variety of programming paradigms. Environment variables do not occur in expressions, being still visible to a programmer either in PFL textual form or in an equivalent form of control driven data flow graphs.